Effect of Warming Anesthetic Solution on Pain Perception During Maxillary Infiltration: A Split Mouth Randomized Control Trial - Saeed, Shahrukh Ahmed; Mahmood, Saad; Baig, Nasir Jamal; Khan, Nazir Ahmed; Rasheed, Nazish; Kakar, Naseer Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the effectiveness of using anesthesia at 42°C (107.6°F) for the insight of pain as dental sedative in contrast to its administration at room temperature 21°C throughout the procedure of maxillary infiltration.Study Design: Double-blind, Split-Mouth randomized clinical trial (Clinical trial number: ISRCTN79560957)Place and Duration of Study: Department of Armed Forces Institute of Dentistry, Rawalpindi, from Jan to Jun 2021.Methodology: A total of 38 patients were examined, undergoing maxillary premolar extractions for orthodontic purposes. Group- A received local anesthesia injection with the anesthesia warmed to 42°C (107.6°F) and group- B patients receiving local anesthesia injection with anesthesia at room temperature. The injection point was placed in the mucobuccal fold apically in the middle of maxillary premolars using a 27G short needle and injecting 0.9 mL of the anesthetics at the speed of 0.15 mL/second. Patients were instructed to grade intensity of pain on Visual analogue scale.Results: According to the Visual analogue scale score, the level of pain perceived with the anesthesia at 42°C (107.6°F) in group-1 was 3.81 ± 1.48 and the level of pain perceived with the anesthesia at temperature 21°C in group-2 was 5.57 ± 1.50 with statistically significant result (p=0.001).Conclusion: The use of anesthesia at 42°C (107.6°F) significantly reduced the pain during the injection of anesthesia compared to its use at room temperature during maxillary injections.